Metabolic hormone FGF21 is induced in ground squirrels during hibernation but its overexpression is not sufficient to cause torpor. - Bethany T Nelson; Xunshan Ding; Jamie Boney-Montoya; Robert D Gerard; Steven A Kliewer; Matthew T Andrews (PLoS ONE)
Hibernation is a natural adaptation that allows certain mammals to survive physiological extremes that are lethal to humans. Near freezing body temperatures, heart rates of 3-10 beats per minute, absence of food consumption, and depressed metabolism are characteristic of hibernation torpor bouts that are periodically interrupted by brief interbout arousals (IBAs). The molecular basis of torpor induction is unknown, however starved mice overexpressing the metabolic hormone fibroblast growth factor 21 (FGF21) promote fat utilization, reduce body temperature, and readily enter torpor-all hallmarks of mammalian hibernation. In this study we cloned FGF21 from the naturally hibernating thirteen-lined ground squirrel (Ictidomys tridecemlineatus) and found that levels of FGF21 mRNA in liver and FGF21 protein in serum are elevated during hibernation torpor bouts and significantly elevated during IBAs compared to summer active animals. The effects of artificially elevating circulating FGF21 concentrations 50 to 100-fold via adenoviral-mediated overexpression were examined at three different times of the year. This is the first time that a transgenic approach has been used in a natural hibernator to examine mechanistic aspects of hibernation. Surgically implanted transmitters measured various metrics of the hibernation phenotype over a 7-day period including changes in motor activity, heart rate and core body temperature. In April fed-state animals, FGF21 overexpression decreased blood insulin and free fatty acid concentrations, effects similar to those seen in obese mice. However, elevated FGF21 concentrations did not cause torpor in these fed-state animals nor did they cause torpor or affect metabolic parameters in fasted-state animals in March/April, August or October. We conclude that FGF21 is strongly regulated during torpor and IBA but that its overexpression is not sufficient to cause torpor in naturally hibernating ground squirrels.